MODERN REQUIREMENTS FOR PROFESSIONAL TRAINING OF SPECIALISTS WITH PHARMACEUTICAL EDUCATION AND THE EDUCATIONAL NEEDS STUDYING OF DRUGSTORES WORKERS - Dmitriy Nikolaevich Kovalev; Valentina Vladimirovna Kulik; Tatyana Georgievna Kovaleva (Современная наука и инновации, 2022)
Highlights qualifications for positions pharmaceutical workers and the procedure for obtaining additional professional education of druggists and pharmacists are lit. By surveying the educational needs of workers studied pharmacy organizations considering duties defined preferred sources of information.